From national loyalty to student political participation: the mediating effect of university citizenship promotion - Watfa, Ali Assad; Ait Ali, Driss (Frontiers in Education, 2025)
IntroductionUniversities have long been regarded as the cornerstone of social transformation. This study explores the role of universities in promoting citizenship values and fostering political participation among university students. Specifically, it examines how national loyalty influences Kuwait university students’ political participation at Kuwait University, with an emphasis on the mediating role of university in promoting citizenship values.MethodsUsing a quantitative approach, data were collected from 1,720 students from different programs.ResultsThe results revealed that national loyalty has a direct and positive effect on students’ political participation, with a partial mediation effect of universities.ConclusionThe findings highlight the importance of both nurturing national loyalty and strengthening universities’ roles in civic education to encourage broader community engagement.